Bridging Times and Spaces : Honouring Gregory E. Areshian on the Occasion of His Sixty-Fifth Birthday. - Avetisyan, Pavel S. (Archaeopress, 2017)
This book presents papers written by colleagues of Professor Gregory E. Areshian on the occasion his 65th birthday. The range of topics includes Near Eastern, Mediterranean and Armenian archaeology, theory of interpretation in archaeology and art history, interdisciplinary history, historical linguistics, art history, and comparative mythology.